Temporalny wymiar osobowości. Panorama stanowisk - Zając-Lamparska, Ludmiła (Wydawnictwa AGH, 2013)
The aim of this article is to review and analyze the psychological concepts of personality in terms of the presence of time issue (in them). The analysis shows that the time can play a role of an external criterion for the description of the functioning of the personality, or be present in the personality itself as psychological time. Status of time issues in psychology of personality has evolved from a secondary problem, which was a kind of background for the most important matters and just signaled, to the central problem which is the primary subject of concern, debate and research. Nowadays, temporal aspects of personality are analyzed and empirical studied, especially in the cognitive approach.

Celem artykułu jest dokonanie przeglądu i analizy psychologicznych koncepcji osobowości pod kątem obecności w nich zagadnienia czasu. Przeprowadzona analiza pozwala stwierdzić, że czas może pełnić rolę zewnętrznego kryterium opisu funkcjonowania osobowości bądź być obecnym w samej osobowości i jako czas psychologiczny. Status zagadnienia czasu w psychologii osobowości ewoluował od problemu wtórnego, stanowiącego swoiste tło dla ważniejszych kwestii i tylko sygnalizowanego, do centralnego, stanowiącego podstawowy przedmiot rozważań, dyskusji i badań. Współcześnie temporalne aspekty osobowości są poddawane analizie i badaniom empirycznym przede wszystkim w nurcie poznawczym.
Temporal dimension of personality. The review of different approaches
Studia Humanistyczne AGH
Keywords: personality; psychological time; osobowość; temporal perspective; czas psychologiczny; perspektywa temporalna; temporal orientation; orientacja temporalna